16.6 times because if there is 3 numbers you simply divide it into 50
ANSWER IS C because I looked it up
Start by distributing the 6 through the parenthses on the left side.
So we have 6x + 24 = 30.
Solving from here, I would subtract 24 from both sides to get 6x = 6.
Finally, dividing both sides of the equation by 6, we have x = 1.
Answer:
The general equation following the pattern becomes is 7 + (n - 1)×2
Where, n = The figure number - 1
Step-by-step explanation:
The pattern in the question can be described as follows;
Figure 2 = (5 + 2) squares boxes = 7 squares boxes
Figure 3 = (5 + 2 + 2) squares boxes
Figure 4 = (5 + 2 + 2 + 2) squares boxes
Therefore, the number of squares boxes per figure, form an arithmetic progression (a + (n - 1)d) with the first term a = 7, the common difference d = 2, and the n = the nth term of the series, such that the general equation following the pattern becomes;
7 + (n - 1)×2.